Matematika dan Budaya: Rancangan Masalah Pola Bilangan Dengan Menggunakan Tenun Ikat Amarasi Barat - Irna Karlina Sensiana Blegur (Mandalika Mathematics and Educations Journal, 2023)
Since the last six decades, linking mathematics and culture has been done. Experts believe that mathematics (whether published or not) was born and developed due to human activity. Therefore, building a mathematics learning environment in the classroom can be done by teachers based on daily activities including cultural activities, especially for students in remote areas. One of the local cultures that is the pride for the people of East Nusa Tenggara, Indonesia is woven fabrics. This is one of the cultural objects, where various philosophies of life that have existed since prehistoric times are embodied. Therefore, weaving, and woven fabrics can be used as a material for learning mathematics. Based on the results of mathematical and cultural studies on woven fabrics of the West Amarasi Society-a small village in East Nusa Tenggara, this paper discusses how to design a number pattern problem. This topic is often considered a difficult topic for local junior high schoolers because the context that is taught is barely visible in everyday life. Further how to implement the designed problem into classes is also discussed in this article